Scott, Mark; Gallent, Nick i Gkartzios, Menelaos (ed.) (2019). The Routledge Companion to Rural Planning - Paül, Valerià (Documents d'Anàlisi Geogràfica, 2020)
Scott, Mark; Gallent, Nick i Gkartzios, Menelaos (ed.) (2019) The Routledge Companion to Rural Planning Londres / Nova York: Routledge, 670 p. ISBN 978-1-138-10405-1